则an+1-(n+1)an=4[an-nan-1]-4[an-1-(n-1)an-2].…2分
即bn+1=4bn-4bn-1.又b1=1,b2=0,所以bn+1-2bn=2(bn-2bn-1),b2-2b1=-2≠0.
所以{bn+1-2bn}是首项为-2,公比为2的等比数列. …4分b2-2b1=-2,所以bn+1-2bn=2n-1(b2-2b1)=-2n.
两边同除以2n+1,可得
bn+1 |
2n+1 |
bn |
2n |
1 |
2 |
于是{
bn |
2n |
1 |
2 |
1 |
2 |
所以
bn |
2n |
b1 |
2 |
1 |
2 |
n |
2 |
(Ⅱ)an-2n=nan-1-n2n-1=n(an-1-2n-1),令cn=an-2n,则cn=ncn-1.
而c1=1,∴cn=n(n-1)•…•2•1•c1=n(n-1)•…•2•1.
∴an=n(n-1)•…•2•1+2n. …12分nan=n•n•(n-1)•…•2•1+n2n=(n+1)!-n!+n•2n,
∴Sn=(2!-1!)+(3!-2!)+…+(n+1)!-n!+(1×2+2×22+…+n×2n).…14分
令Tn=1×2+2×22+…+n×2n,①
则2Tn=1×22+2×23+…+(n-1)×2n+n×2n+1.②
①-②,得-Tn=2+22+…+2n-n×2n+1,Tn=(n-1)2n+1+2.
∴S^=(n+1)!+(n−1)2n+1+1.…16分.